Pengaruh Persepsi Keaslian Influencer Terhadap Promosi Dari Mulut Ke Mulut Konsumen: Peran Mediasi Kredibilitas Influencer - Jafar Muhammad Muslih; Farida Indriani (Faculty of Economics and Business Diponegoro University, 2026)
The rapid development of social media has transformed how consumers receive information and make purchasing decisions. Influencers, as influential figures on social media platforms, play a significant role in shaping consumer perceptions and behaviors. This study aims to analyze the effect of influencer authenticity; comprising originality, naturalness, and consistency on consumer Word of Mouth (WOM), with influencer credibility including attractiveness, trustworthiness, and expertise as the mediating variable. This research employs a quantitative method using Structural Equation Modeling (SEM). The sample consists of 200 respondents, specifically students of Diponegoro University who use Instagram and follow at least one influencer. Data were collected using a 7-point Likert scale questionnaire. The analysis was conducted using SPSS 22, AMOS 26, and LISREL 8.7. The findings indicate that Originality positively influences attractiveness but negatively affects trustworthiness. Naturalness positively influences attractiveness but has no significant effect on trustworthiness. Consistency positively influences trustworthiness and expertise. All three dimensions of credibility—attractiveness, trustworthiness, and expertise—positively influence PWOM. Influencer credibility mediates the relationship between influencer authenticity and PWOM. This study contributes to the theoretical understanding of influencer marketing and provides practical implications for companies and influencers in optimizing their social media marketing strategies.